Geometry for college students - Isaacs, I. Martin (American Mathematical Society Rhode Island, USA, 2013)
The book begins with a thorough review of high school geometry, then goes on to discuss special points associated with triangles, circles and certain associated lines, Ceva's theorem, vector techniques of proof, and compass-and-straightedge constructions. There is also some emphasis on proving numerical formulas like the laws of sines, cosines, and tangents, Stewart's theorem, Ptolemy's theorem, and the area formula of Heron. (http://www.ams.org/bookstore-getitem/item=amstext-8)
Keywords: Geometry - Textbooks